2021
DOI: 10.3390/v13030495
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Bacteriophage CL31 and Interaction with the Host Strain Corynebacterium glutamicum ATCC 13032

Abstract: In this study, we provide a comprehensive analysis of the genomic features of the phage CL31 and the infection dynamics with the biotechnologically relevant host strain Corynebacterium glutamicum ATCC 13032. Genome sequencing and annotation of CL31 revealed a 45-kbp genome composed of 72 open reading frames, mimicking the GC content of its host strain (54.4%). An ANI-based distance matrix showed the highest similarity of CL31 to the temperate corynephage Φ16. While the C. glutamicum ATCC 13032 wild type strain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 79 publications
3
5
0
Order By: Relevance
“…As with the Tn-Seq analysis, the majority of the isolates had mutations in genes required for mycolic acid synthesis ( Figure 7—Table supplement 1 ), such as fadD2, pccB, and otsA or genes known to be associated with defects in mycolic acid synthesis, such as deoC (41). These findings were consistent with a recent report in which pks and pccB mutations were also found to promote CL31 resistance (17). In addition to mutations in well-characterized genes, we also isolated phage resistant alleles in a gene of unknown function, cgp_0475, including a five-codon duplication (+EVLPL) within the reading frame.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…As with the Tn-Seq analysis, the majority of the isolates had mutations in genes required for mycolic acid synthesis ( Figure 7—Table supplement 1 ), such as fadD2, pccB, and otsA or genes known to be associated with defects in mycolic acid synthesis, such as deoC (41). These findings were consistent with a recent report in which pks and pccB mutations were also found to promote CL31 resistance (17). In addition to mutations in well-characterized genes, we also isolated phage resistant alleles in a gene of unknown function, cgp_0475, including a five-codon duplication (+EVLPL) within the reading frame.…”
Section: Resultssupporting
confidence: 94%
“…Most of the plaques were large and turbid, but a small percentage were small and clear. A similar heterogeneity in plaque morphology for lab-adapted CL31 was recently reported, but the cause of the phenomenon was not investigated (17). Phage purified from the clear plaques retained this phenotype and gave rise to only clear plaques on the MB001 host (Figure 1B).…”
Section: Adaptation Of Environmental Corynephages To the Laboratory C...supporting
confidence: 72%
See 1 more Smart Citation
“…Most of the plaques were large and turbid, but a small percentage were small and clear. A similar heterogeneity in plaque morphology for lab-adapted CL31 was recently reported, but the cause of the phenomenon was not investigated ( Hünnefeld et al, 2021 ). Phage purified from the clear plaques retained this phenotype and gave rise to only clear plaques on the MB001 host ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 56%
“…Whole-genome sequencing of the clear plaque CL31 isolate ( CP CL31) identified single nucleotide polymorphisms (SNPs) in the 3’ end of clg55 , which encodes a predicted tail protein in the structural protein locus of the genome ( Figure 1—source data 1 ). Notably, previous work has identified a putative variable region within Clg55, independent of the region in which these mutations occur ( Hünnefeld et al, 2021 ), suggesting that clg55 is under selection, possibly due to its role in receptor recognition. Four additional CP CL31 variants were isolated, and Sanger sequencing revealed that all also had mutations in clg55 , further implicating this structural gene in the altered plaque morphology phenotype ( Figure 1—source data 1 ).…”
Section: Resultsmentioning
confidence: 97%